Pembuatan Katalog Digital dan Cetak Alat Teknologi Tepat Guna Hasil Pengabdian Masyarakat DRTPM Tahun 2019-2024 LPPM Universitas - Ahmed David Anugerah; Anik Anekawati; Abshoril Fithry (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2025)
The Wiraraja University Research and Community Service Institute (LPPM) has implemented various community service programs which have produced various appropriate tools and technology during the 2019-2024 period. However, the results of this service have not been well documented and have not been widely published, so its use by the community is still considered limited. The aim of this activity is to compile and publish digital and printed catalogs containing complete information regarding appropriate tools and technology resulting from community service by LPPM Wiraraja University during the 2019-2024 period. It is hoped that this catalog can become a reference that is easily accessible to the public, government and other related parties, so that it can increase the use and adoption of the technology that has been developed. The targeted output in this activity is the creation of a catalog which contains and documents appropriate tools and technology resulting from DRTPM community service during the 2019-2024 period under LPPM Wiraraja University in PDF format and web-based applications at issue.com for digital catalogs and books or magazines for printed catalogues.